Scenario Planning Development for Food Advertising Supervison in Digital Media Distruption Era - Sarah, Shanty; Siallagan, Manahan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The number of digital advertising channels is expected to overgrow in the future. The overgrowth of digital advertising will potentially increase the risk of advertising that does not comply with the requirements. Food advertising control will continue to face uncertainties in the future. Food and beverage companies have spotted opportunities in integrated communication in digital advertising such as programmatic advertising, advergames, native advertising, unidentified advertising by influencers, and blockchain advertising, which are expected to grow in the next five years. The key focal issue of this research is how digital media technology will affect the supervision of food advertising in Indonesia over the next five years. The study involved expert representatives from the Indonesian FDA, Provincial Health Office, Ministry of Communication and Informatics, University, Broadcasting Committee, Association of Advertising Companies, Food and Beverage Company Association, and e-commerce Association. Through in-depth interviews, 17 driving forces were identified and two critical uncertainties were defined. Those two critical uncertainties, digital technology advancement and digital literacy are formulated into four scenario frameworks. The research also constructs the early warning signals and indicators that distinguish one scenario from another. Scenario planning enables an organization to anticipate the uncertain future and its consequences, which necessitates carefully planning strategic responses to future opportunities and threats.